Cy Young : an American baseball hero - Longert, Scott (Biographies for young readers., 2020)
Chronicles the life and career of Cy Young, professional baseball player, and details his childhood, his career with the Boston Red Sox and Cleveland Indians, and his legacy. Presents the history of Major League Baseball including the American League and the National League, and explains the rules of baseball. Includes black-and-white photographs, a timeline, a glossary, and additional resources.